Antibacterial and antibiofilm activity of halogenated phenylboronic acids against Vibrio parahaemolyticus and Vibrio harveyi - Sathiyamoorthi, Ezhaveni; Lee, Jin-Hyung; Lee, Jintae (Frontiers in Cellular and Infection Microbiology, 2024)
Vibrios are associated with live seafood because they are part of the indigenous marine microflora. In Asia, foodborne infections caused by Vibrio spp. are common. In recent years, V. parahaemolyticus has become the leading cause of all reported food poisoning outbreaks. Therefore, the halogenated acid and its 33 derivatives were investigated for their antibacterial efficacy against V. parahaemolyticus. The compounds 3,5-diiodo-2-methoxyphenylboronic acid (DIMPBA) and 2-fluoro-5-iodophenylboronic acid (FIPBA) exhibited antibacterial and antibiofilm activity. DIMPBA and FIPBA had minimum inhibitory concentrations of 100 μg/mL for the planktonic cell growth and prevented biofilm formation in a dose-dependent manner. Both iodo-boric acids could diminish the several virulence factors influencing the motility, agglutination of fimbria, hydrophobicity, and indole synthesis. Consequently, these two active halogenated acids hampered the proliferation of the planktonic and biofilm cells. Moreover, these compounds have the potential to effectively inhibit the presence of biofilm formation on the surface of both squid and shrimp models.